ABDIMAS HIDROPONIK SEBAGAI BASIS PENINGKATAN PEREKONOMIAN MASYARAKAT PADA PKK BANJAR DELOD PANGKUNG DESA SUKAWATI, KECAMATAN SUKAWATI KABUPATEN GIANYAR - Putu Eka Pasmidi Ariati; Ni Putu Cempaka Dharmadewi Atmaja; Ni Made Satya Utami (Jurnal Bakti Saraswati (JBS): Media Publikasi Penelitian dan Penerapan Ipteks, 2018)
PKK Banjar Delod Pangkung is one of the PKK active in various government programs. Most PKK members are housewives who do not work formally. Day-to-day activities are used by mothers to meet, brama and parenting their children. Of course with these activities there is still plenty of free time available to develop hydroponics vegetables in the yard. The development of hydroponics vegetables in addition to beautify the yard and provide nutrient intake for the family also provides economic benefits to support the family economy. Hydroponic vegetables usually have short harvest periods, excess yields can be sold so that they can add to household income. The problems encountered through interviews and in-depth discussions with the head of the Banjar Delod Pangkung Environmental Office, namely members of the PKK are housewives who work in the non-formal sector such as traders in small stalls, caseworkers and some as farmers so that household income is still which is still relatively low. PKK has not been able to utilize the home yard as one source of family income. Expected output targets are (1) Hydroponic Farming System becomes one of the business opportunities that can improve quality, quantity and added value continuously. (2) Production of hydroponics vegetables can meet the needs of household at any time even the excess of harvest can be sold. (3) Increasing the value of community science and technology on PKK Banjar Delod Pangkung Desa Sukawati, Sukawati District Gianyar Regency.